Perancangan Aplikasi Sistem Presensi Guru Berbasis Web Menggunakan Geo Fencing Pada Sekolah SDN XYZPerancangan Aplikasi Sistem Presensi Guru Berbasis Web Menggunakan Geo Fencing Pada Sekolah SDN XYZ - Faizul Anwar Ramdhani; Cahyono Budy Santoso (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
The web-based teacher attendance system application with Geo-Fencing technology integration is designed to improve the accuracy and efficiency of the teacher attendance recording process in the school environment. The use of Geo-Fencing allows attendance to only be done when the user is in a predetermined area, thus minimizing the potential for fraud and data manipulation. This research aims to develop a web-based attendance application and evaluate its usability level using the System Usability Scale (SUS) method. The evaluation was conducted on 20 respondents consisting of teachers and school administrators. Based on the test results, an average SUS score of 75 was obtained, which is included in the Good usability category. Thus, this application is considered quite easy to use, effective, and acceptable to users. The results of this study indicate that the web-based teacher attendance system application with Geo-Fencing has the potential to be widely implemented in the school environment, with some further development recommendations to improve user experience.